Exploring the Impact of Digital Literacy on Cognitive Development in Early Childhood Education: A Systematic Literature Review - Karnita, Anggun; Aisyah, Siti; Mustapa, Noviana; Siti Syarah, Erie; Raymena Jovanka , Della; bt Mahamud, Samihah (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – This systematic literature review explores the development of digital literacy among children in the post-typographic era, where digital technology increasingly dominates daily life. The purpose of this study is to identify the impact of digital literacy on various dimensions of cognitive development in young children, including early numeracy, executive functioning, critical thinking, and creativity. By broadening the conceptualization of cognitive development, this study aims to provide a comprehensive understanding of how digital literacy contributes to children's intellectual growth in early childhood education.Design/methods/approach – Analysis of 33 studies obtained from the period between 2019 and 2024 indicates that children engage in multimodal practices, using technology for both play and learning. This highlights the importance of educators' understanding of digital literacy practices at home. Factors such as children's age, family structure, household income, and Human Development Index (HDI) significantly contribute to predicting preschool children's early digital literacy.Findings – The findings show that while children's literacy skills may benefit from access to digital resources, their mathematical skills do not demonstrate significant improvement. However, this study recommends that teachers collaborate with parents to enhance digital literacy and awareness of digital data security. Additionally, the use of interactive digital media can increase children's engagement and motivation in learning, allowing for more differentiated and inclusive learning approaches.Research implications/limitations – Future research should prioritize the development of age-appropriate, culturally relevant, and innovative digital content that can support effective teaching and learning in the digital age. Additional longitudinal studies are needed to explore the long-term cognitive and socio-emotional effects of digital media exposure in early childhood.Practical implications – Digital literacy can help children develop critical thinking, problem-solving, and creativity skills. However, exposure to age-inappropriate content can hinder their social-emotional development. The conclusion of this study emphasizes the need for training and support for educators in using digital media, as well as close collaboration with parents to ensure the successful implementation of digital literacy in early childhood education.Originality/value – This review offers a novel contribution by integrating multiple dimensions of cognitive development with the concept of digital literacy. It provides valuable insights into the future of educational practices, emphasizing the importance of digital competencies as foundational elements in early childhood education in the digital era.Paper type Literature review